Pine Rhizosphere Soil Microorganisms Enhance the Growth and Resistance of Pinus massoniana Against Nematode Infection - Jiacheng Zhu; Chenxi Deng; Yichi Zhang; Manman Liu; Guoying Zhou; Junang Liu (Microorganisms)
Pine wilt disease, caused by Bursaphelenchus xylophilus, poses severe ecological and economic threats to coniferous forests. This study isolated two fungal (Arthropsis hispanica, Penicillium sclerotiorum) and two bacterial (Bacillus amyloliquefaciens, Enterobacter hormaechei) strains from Pinus massoniana rhizospheres, evaluating their biocontrol potential against pine wood nematodes. Molecular characterization confirmed strain identities. In vitro assays demonstrated that combined fermentation filtrates of CSX134+CSZ71 and CSX60+CSZ71 significantly enhanced plant growth parameters (height, biomass) and root-associated soil enzyme activities (urease, acid phosphatase) in P. massoniana. Treated plants exhibited elevated defense enzyme activities and upregulated defense-related gene expression. The treatments achieved 75.07% and 69.65% nematode control efficacy, respectively, compared to controls. These findings highlight the potential of microbial consortia in activating systemic resistance and suppressing pine wilt disease through the dual mechanisms of growth promotion and defense induction.